Structural, chemical and osteogenic properties of GNS reinforced fluorine-doped strontiumapatite coatings on AZ31 Mg alloys for potential biomedical applications - Yigit, Oktay (Elsevier Science Sa, 2022)
Different ion-doped composite coatings, especially graphene and fluorine-substituted apatite coatings, are intensely interested in surface modifications of different metallic implants for medical applications due to their excellent biological and chemical properties. However, their use in clinical applications in metallic implant materials is limited due to unsuitable biomechanical properties, low corrosion resistance, insufficient osteoin-ductivity, and bioactivity capacities. In this study, Graphene Nanosheet (GNS) and F-substituted SrAp (SrFAp/ GNS) composite coatings were deposited on AZ31 magnesium substrate by hydrothermal method, and the effects of different GNS additives on SrFAp composite were reported for the first time. Morphological investigations showed crystals of SrFAp structures of GNS to grow in a needle-like structure and transform into a bone-like nano-needle structure. In addition, these structures began to transform into a more porous leaf form in the simulated body fluid. GNS layers also improved the surface properties and cell adhesion ability by developing a porous and rough coating morphology. With the GNS additive, the wettability properties of the composite coating were also significantly increased. In addition, the corrosion resistance of the examined coatings was significantly improved with the increasing GNS ratio. Co-doping of F and GNS in SrFAp/GNS coatings also improves the cytocompatibility of the SrAp construct. SrFAp/GNS composites significantly promote cell adhesion and proliferation and do not show any adverse toxic behavior. Therefore, SrFAp/GNS coated AZ31 Mg alloys, with their combination of high cytocompatibility, good mechanical properties, and superior corrosion resistance compared to Mg alloys, have shown promising results for clinical implant applications.
Keywords: Graphene; Ion-doped apatite; Osteogenic properties; In-vitro corrosion; Mg alloys